Posthumanism: a critical analysis - Herbrechter, Stefan (Bloomsbury, 2013)
Towards a critical posthumanism -- Genealogy of posthumanism -- Our posthuman humanity and the multiplicity of its forms -- Posthumanism and science fiction -- Interdisciplinarity and the posthumanities -- Posthumanism, digitalization, and new media -- Posthumanity, subject, and system -- Other side of life.
Includes bibliographical references and index
Keywords: Electronic books; Posthumanismus